Life cycle cost assessment and multi-criteria decision analysis of environment-friendly building insulation materials - A review - Zhao, Jianjun; Li, Shuang (Energy and buildings, 2022)
[Display omitted] •A comprehensive review of the application of solid waste in building insulation materials.•Solid waste mainly comes from municipal, industry and agriculture.•Life cycle cost, annual power consumption and pollutant gas emissions were calculated.•Based on the decision analysis method, the most promising building insulation material was determined. The effective application of solid waste in building insulation materials is of great significance to the global economic and social development, because energy shortages and environmental pollution are two global problems that need to be solved urgently. However, unfortunately, there are few, or no systematic studies on this aspect. In order to fill this gap, solid waste was divided into municipal solid waste, industrial solid waste and agricultural solid waste according to the source. The bulk density, thermal conductivity, water absorption and compressive strength of three types of solid waste recycled building insulation materials were systematically evaluated. The relationships between bulk density and thermal conductivity and compressive strength were given, respectively. For solid waste recycled building insulation materials with poor thermal performance and flame retardancy, corresponding improvement suggestions were put forward. Taking a city as an example, the life cycle cost (LCC), energy consumption and gas emissions were discussed in detail. Based on the decision analysis method, the most promising building insulation material was selected. Finally, in view of the shortcomings of the existing study, the future study direction in this field was proposed.